Efektifitas Penerapan Multi-Criteria Decision Making (Mcdm) Dalam Pemilihan Perangkat Lunak Layanan Pengolah Pemungutan Suara Elektronik Dengan Menggunakan Expert Choice - Faisal Faisal (KILAT, 2016)
The voting process conducted service today is still done manually so that it becomes a decision to utilize the electronic voting (e-voting) processing services. E-voting greatly reduce human control and direct their influence on this process. Provide an opportunity to resolve some of the problems that have long election but also provide a series of new concerns. Problems faced by end users in the selection is there are so many choices of software processing electronic voting services based on Information Communication Technology (ICT). Decision-making, essentially a form of election of the various alternatives of action or multi-criteria decision making (MCDM) that can be selected. In this research, decision support system (DSS) is used to select the type of service software processing electronic voting. The method used is the Multi-Criteria Decision Making (MCDM) and Analytical Hierarchy Process (AHP) using "Expert Choice 2000TM" software computer. And aims to make decisions that can help make certain parties to take the best decision in choosing the type of software processing services electronic voting. From the data processing is concluded that the first sequence is Online voting, ExpressVote second, Simply voting third, and Ballot Online fourth.